PENGARUH KEPEMILIKAN INSTITUSIONAL, KOMPETENSI DEWAN KOMISARIS DAN KUALITAS AUDITOR PADA NILAI PERUSAHAAN - Ratna Sari Dewi, Cok Istri; Dwi Ratnadi, Ni Made; M. Ratna Sari, Maria (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
High firm value will increase the prosperity of shareholders. The higher the stock price, the higher the firm value could be. Generally investors will hand over its management to the professionals to achieve the company’s goal which is to increase the firm values. This study aims to examine the influence of institutional ownership, the competence of board of commissioners and the quality of auditor on firm values. The analyzed data is secondary data, taken from financial statements and annual reports of companies that listed in Indonesia Stock Exchange from 2012-2015. The sample selection determined by using purposive sampling technique, 48 companies were acquired. Multiple linear regression techniques were used to analyze the data. The results showed that institutional ownership, the competence of board of commissioners and the quality of auditor have positive effects on firm values.
Keywords: institutional ownership, the competence of board of commissioners, the quality of auditor, firm values.